ANALISIS HASIL BELAJAR PESERTA DIDIK DALAM LITERASI MEMBACA MELALUI STUDI INTERNASIONAL (PIRLS) 2011 - Maman Suryaman (LITERA, 2015)
AbstractThis study aims to describe: (a) Indonesian students’ reading skills in the internationallevel, (b) their skills in solving literary and non-literary test items, and (c) factors affectingtheir problem solving skills. This study employed the exploratory descriptive approachand document analysis. The data source was the database of IEA Program PIRLS 2011taken from PIRLS-almanac and TPIRLS-item released. The results of the study are asfollows. First, the average attainment of Indonesian students’ reading skills is lower thanthe international median. Second, their problem solving skills improved from 2006 to 2011,especially in the high, moderate, and low levels, but there was no improvement in theexcellent level. Third, the problem solving skills are affected by: (a) a tendency to answerquestions by guessing, (b) the poor construction of stems and options, (c) poor qualitydiscourses, (d) reading competence development which is not maximum, (e) inadequatereading habit development, (f) inappropriate literary theories taught, (g) answers whichare varied according teachers and students, and (h) test items that do not usually appearin the national examination.Keywords: reading skills, national examination, literary and non-literary test items